2018
DOI: 10.1115/1.4040491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Grasping Performance of Tendon and Linkage Transmission Systems in an Electric-Powered Low-Cost Hand Prosthesis

Abstract: The popularization of fused deposition modeling (FDM) technology and open-source microcontrollers has permitted the explosion of electric hand prostheses that can be designed, shared, built, and operated at a low cost, under the Do It Yourself premise. Patients with limb reductions at the transcarpal or transradial level are best candidates to benefit from them. They manage the gross location with the remaining limb, while the built-in motors offer the possibility of controlling each finger independently. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Notwithstanding, some important aspects in the design of an artificial hand are not within the scope of the AIM: the orientation of the joint axes, the range of motion of the different hand joints, the dimension of the phalanges, the friction coefficient of the parts of the hand in contact with the objects, the grasping force exerted by the actuators, the efficiency of the driving linkages, the control system, etc. Some previous studies [3335] have shown the relevance of these aspects. In this sense, the AIM, involving mainly the topological structure, the number of actuators, and the type of underactuation, can be considered as an index especially useful in the concept design stage.…”
Section: Resultsmentioning
confidence: 89%
“…Notwithstanding, some important aspects in the design of an artificial hand are not within the scope of the AIM: the orientation of the joint axes, the range of motion of the different hand joints, the dimension of the phalanges, the friction coefficient of the parts of the hand in contact with the objects, the grasping force exerted by the actuators, the efficiency of the driving linkages, the control system, etc. Some previous studies [3335] have shown the relevance of these aspects. In this sense, the AIM, involving mainly the topological structure, the number of actuators, and the type of underactuation, can be considered as an index especially useful in the concept design stage.…”
Section: Resultsmentioning
confidence: 89%
“…Three of the most common 3D-printed electrical prosthetic hands for transradial amputees currently available online, with documented clinical usage, were chosen for the present study, namely (Andrés et al, 2019 ), the Dextrus v2.0, the InMoov, and the Limbitless hands. Together with the IMMA hand, designed by the authors (Llop-Harillo and Pérez-González, 2017b ), Table 1 summarizes each of the mechanical design characteristics as outlined by Controzzi et al ( 2014 ) and summarized in the previous section.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the use of OpenHand and the methodologies described in this Chapter have been used to evaluate prosthetic hand designs in: Llop-Harillo et al, 2017;Cardín-Catalán et al, 2016;Llop-Harillo et al, 2018;Andrés et al, 2018.…”
Section: Future and Related Workmentioning
confidence: 99%